Age as a determinant of survival in HIV infection. - Babiker, A; Peto, T; Porter, K; Walker, A; Darbyshire, J (2001)
Age is a major determinant of mortality for many diseases including HIV infection, yet the effect of age is rarely studied directly. In this article, we review what is known about the effect of age at seroconversion on HIV disease progression and survival prior to the widespread use of HAART before describing appropriate methods for adjusting for background mortality in more detail. We then investigate the impact of HAART on the effect of age at seroconversion on mortality and consider the estimation of the age effect in seroprevalent cohorts with regard to lack of knowledge of the true age at infection. Finally, we discuss mechanisms by which age at seroconversion might impact on disease progression and death. Throughout, we use published results by the Collaborative Group on AIDS Incubation and HIV Survival (CGAIHS), and published results and data from the Concerted Action on SeroConversion to AIDS and Death in Europe (CASCADE) for illustration.